Frontiers of the Ottoman imagination: studies in honour of Rhoads Murphey - Hadjianastasis, Marios (Brill, 2015)
"Frontiers of the Ottoman Imagination is a compilation of articles celebrating the work of Rhoads Murphey, the eminent scholar of Ottoman studies who has worked at the Centre for Byzantine, Ottoman and Modern Greek Studies at the University of Birmingham for more than two decades. This volume offers two things: the versatility and influence of Rhoads Murphey is seen here through the work of his colleagues, friends and students, in a collection of high quality and cutting edge scholarship. Secondly, it is a testament of the legacy of Rhoads and the CBOMGS in the world of Ottoman Studies. The collection includes articles covering topics as diverse as cartography, urban studies and material culture, spanning the Ottoman centuries from the late Byzantine/early Ottoman to the twentieth century. Contributors include: Ourania Bessi, Hasan Çolak, Marios Hadjianastasis, Sophia Laiou, Heath W. Lowry, Konstantinos Moustakas, Claire Norton, Amanda Phillips, Katerina Stathi, Johann Strauss, Michael Ursinus, Naci Yorulmaz"--Provided by publisher
Keywords: Turkey -- History -- Ottoman Empire, 1288-1918; Turkey -- Civilization -- 1288-1918; Aufsatzsammlung; Festschrift; Zivilisation; Geschichtsschreibung; Einbildungskraft; Türken; Kultur; Geschichte; Türkei; Osmanisches Reich